An improved spiral dynamic algorithm and its application to fuzzy modelling of a twin rotor system - Nasir, A. N. K.; Tokhi, M. O.; Omar, M. E.; Ghani, N. M. A. (2014 World Symposium on Computer Applications & Research (WSCAR), 2014)
This paper presents the development of an improved spiral dynamic optimisation algorithm with application to fuzzy logic dynamic modelling of a twin rotor system. Spiral motion and dynamic step size generated by a spiral model produce unique exploration and exploitation strategies of a spiral dynamic algorithm. However, the algorithm is subject to settling into local optima at the end of the search process due to insufficient exploration throughout the search area. An elimination and dispersal strategy of a bacterial foraging algorithm is adopted to solve the problem. Moreover, the application of acquiring nonlinear dynamic model of a helicopter model prototype in hovering mode is presented and the results show the effectiveness of the proposed algorithm to solve real world problems. The result of the modelling work is presented in both time-domain and frequency-domain. It shows that the fuzzy model optimized by the proposed algorithm is better and adequate to represent the characteristic behaviour of the helicopter model prototype system.